Research handbook on the economics of tax havens - Lejour, Arjan 1966-; Schindler, Dirk 1974- (Edward Elgar Publishing, 2024)
"This Research Handbook provides a broad overview of research on tax havens within the fields of economics and accounting, as well as political science and tax law. Covering both corporate income tax avoidance and personal income tax evasion, it investigates their profound impact on individuals, multinational firms, governments and the global economy as a whole. Expert authors examine the magnitude of tax revenue losses stemming from tax havens, and identify their key characteristics and activities. Chapters analyse the many business models adopted by tax havens, including conduit countries, hidden havens and crime havens. Drawing on cross-disciplinary insights, the Research Handbook evaluates the successes and failures of policy initiatives to prevent tax avoidance and evasion. Reflecting on the increased attention paid to tax havens since the 2008/09 economic crisis, it identifies promising avenues for future research and regulation in the field. The Research Handbook on the Economics of Tax Havens is an invaluable resource for students and scholars of economics, accounting, tax law, finance and political science. It is also an important read for policy makers seeking to reduce tax avoidance and evasion"--...
Keywords: Aufsatzsammlung